Artificial Sweeteners: Chemistry, Health Impacts and Regulatory Perspectives - Manish Sachan,; Pushpraj Singh, (Asian Journal of Pharmaceutical Research and Development, 2025)
Artificial sweeteners are substances that mimic the taste of sugar but offer negligible or zero calories. Their discovery dates back to the 19th century with saccharin. With the rise in lifestyle diseases like obesity, diabetes etc, their role as sugar alternatives has become increasingly significant. Therefore, food industries use various artificial sweeteners that are used in weight loss, diet planning with no calories or low calorie contents instead of high calorie sugar. These sweeteners are used instead of sucrose to sweeten the product. In recent years, these are used in over 6000 or more products. United States Food and Drug Administration (US FDA) has approved aspartame, acesulfame-K, neotame, sodium cyclamate etc for use as per acceptable daily intake (ADI) value. This paper aims to provide a comprehensive overview about the introduction, structure, possible health benefits and concerns of artificial sweeteners.